2020
DOI: 10.1021/acsami.0c00328
|View full text |Cite
|
Sign up to set email alerts
|

Light-Triggered Reversible Supracolloidal Self-Assembly of Precision Gold Nanoclusters

Abstract: Monolayer thiol-protected noble metal nanoclusters are attractive nanoscale building blocks for well-defined colloidal superstructures. However, achieving facile reversible self-assembly of nanoclusters using external stimuli is still in its infancy. Herein, we report the synthesis and photon-assisted reversible self-assembly of thiolated azobenzene-stapled Au25 nanoclusters. Photoactivation of functionalized nanoclusters in dichloromethane by irradiating ultraviolet light at 345 nm resulted in a visual change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Rival et al developed a light-triggered strategy for stacking thiolated azobenzene-protected Au 25 NCs into disk-like superstructures, where light-switchable dipole–dipole interactions of azobenzene govern the self-assembly behaviour of NCs. 193 Moreover, H-bonds have also been employed by Nonappa et al for packing Au 102 ( p -MBA) 44 into 2D nanosheets, which can be further bent into spherical capsids or stacked into faceted multi-layers ( Fig. 7c ).…”
Section: Molecular Interactions/reactions In Post-synthesis Development Of Metal Ncsmentioning
confidence: 99%
“…Rival et al developed a light-triggered strategy for stacking thiolated azobenzene-protected Au 25 NCs into disk-like superstructures, where light-switchable dipole–dipole interactions of azobenzene govern the self-assembly behaviour of NCs. 193 Moreover, H-bonds have also been employed by Nonappa et al for packing Au 102 ( p -MBA) 44 into 2D nanosheets, which can be further bent into spherical capsids or stacked into faceted multi-layers ( Fig. 7c ).…”
Section: Molecular Interactions/reactions In Post-synthesis Development Of Metal Ncsmentioning
confidence: 99%
“…investigated the photon‐assisted switchable self‐assembly in [Au 25 (C 3 ‐AMT) 18 ] − NCs using two different wavelengths of light. [ 313 ] The modified Brust–Schiffrin method [ 96 ] was used to synthesize the kinetically controlled Au 25 NCs using C 3 ‐AMT as the protecting ligand. Photoisomerization of [Au 25 (C 3 ‐AMT) 18 ] − NCs under visible (435 nm) and ultraviolet (345 nm) lights has shown systematic changes in the optical absorption bands and chemical shifts in NMR spectra.…”
Section: Molecular Interactions In Nc Self‐assemblymentioning
confidence: 99%
“…In another approach, small gold nanoclusters (Au 25 ) were coated with azobenzene C3 alkyl monothiol. 39 It was found that for such a system, a transformation from trans to cis form is realized aer exposure to 345 nm light, and the reverse process is observed aer exposure to 435 nm light. Attractive dipoledipole interactions, which occur only for the cis form, lead to a self-assembly of nano-clusters covered with ligands containing the azobenzene moiety in the cis form.…”
Section: Photo-assembly Of Plasmonic Nanoparticlesmentioning
confidence: 99%